On the Category of Sex and Grammatical Gender in the Polish Language - Nowosad-Bakalarczyk, Marta (Vilnius University Open Series, 2020)
The article is concerned with the selected aspects of the relation between sex and gender in the Polish language. The starting point for the discussion is the notion of sex – formed on the basis of the existing (and visible) biological differences in the world of humans and animals, grounded (and reproduced) in culture (i.e. the notion of gender). The aim of the discussion is to realize how these notions are encoded in the Polish language. It has been assumed that the category of biological sex underlies the linguistic category of gender understood, however, broadly, i.e. as a set of heterogenous linguistic forms interrelated by the common content, i.e. the meaning of sex/gender. The description of the category understood this way requires a holistic view of language as a tool for expressing thoughts (relative to its various levels, including the context of use) and also using the procedure “from meaning to form”. In the article, the author presents different types of markers of masculinity and femininity in the Polish language, i.e. lexical, morphological (inflexional and word-formative), textual, and contextual. It has been determined that in the case of concrete instances of language use, one deals with various combinations of the above mentioned indicators.